DEVELOPMENT OF COMMUNICATIVE SKILLS IN PRE-SCHOOL CHILDREN THROUGH THEATER GAMES - Shakhnoza Khasanova; Laziza Zufarova (International Scientific and Current Research Conferences, 2023)
The system of additional education for children as a social institution functions on the basis of the social order of society, provides a wide range of educational services, satisfying the ever-growing individual educational needs of the individual, ensures the effective formation of the personal and social qualities of the pupil, who shows creative initiative, the ability to independently search for new ways of action, desire for self-realization and self-expression.